When metabolic enzymes meet lactylation: a bidirectional dialogue in health and disease - Xiang Zhao; Jia-Hui Liu; Kun-Yao Liu; Guo-Chao Lin; Xiao Liu; Zhen Wang; Xin Zhou (Frontiers in Cell and Developmental Biology, 2026)
Lactate accumulation occurs in diverse physiological and pathological states, including hypoxia, ischemia, development, wound healing, immune activation, and cancer, where it functions as a key regulator of cellular energy metabolism, signal transduction, microenvironmental homeostasis, and immune responses. Protein lactylation was first described in 2019, revealing that lactate can serve as a substrate for post-translational protein modification. This review focuses on the bidirectional interplay between metabolic enzymes and lactylation. On one hand, metabolic enzymes control lactate production and thereby shape the lactylation landscape. On the other hand, lactylation exerts feedback regulation through two mechanisms: directly, lactylation of metabolic enzymes per se alters enzyme properties, including activity, stability, and interactions; indirectly, histone lactylation epigenetically modulates the expression of metabolic enzymes, and the lactylation of other proteins alters the expression or activity of metabolic enzymes. Through this integrated framework, we aim to elucidate how lactylation influences the functional traits of metabolic enzymes and how lactylation of metabolic enzymes, in turn, affects disease onset and progression. Finally, we explore whether targeting lactylation of metabolic enzymes could emerge as a promising therapeutic avenue.